Growing Rural Youth Agribusiness in Kenya: Stories And Best Practices Of The Vijabiz Project - Smith, Georgina; Koigi, Bob; Cartmell-Thorp, Susanna; Reeve, Sophie; Frost, Olivia; Mutimer, Alice (Technical Centre for Agricultural and Rural Cooperation and Ustadi, 2020)
Youth constitute about 30% of the Kenyan population and 60% of the total labour force, with 1 million youth entering the labour market each year. The 2013 UNDP Kenya’s Youth Employment Challenge report revealed that 64% of unemployed Kenyans were youth, which is a critical concern for the country.